2023
DOI: 10.3390/microorganisms12010068
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate and Non-Surgical Periodontal Treatment Change the Oral–Gut Microbiota in Rheumatoid Arthritis: A Prospective Cohort Study

Sicília Rezende Oliveira,
José Alcides Almeida de Arruda,
Jôice Dias Corrêa
et al.

Abstract: This study evaluated the changes in the composition of oral–gut microbiota in patients with rheumatoid arthritis (RA) caused by methotrexate (MTX) and non-surgical periodontal treatment (NSPT). Assessments were performed at baseline (T0), 6 months after MTX treatment (T1), and 45 days after NSPT (T2). The composition of the oral and gut microbiota was assessed by amplifying the V4 region of the 16S gene from subgingival plaques and stools. The results of the analysis of continuous variables were presented desc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…It has been documented that RA can originate from mucosal locations, including the intestine and oral cavity [38]. Several molecular studies have shown that dysbiosis in patients with RA is characterized by the loss of Bacteroidetes with an overgrowth of Prevotella copri (P. copri) in the intestine, also in patients treated with methotrexate [39,40]. This phenomenon is especially common in patients carrying the "shared epitope" [41].…”
Section: Influence Of the Microbiome On Autoimmunitymentioning
confidence: 99%
“…It has been documented that RA can originate from mucosal locations, including the intestine and oral cavity [38]. Several molecular studies have shown that dysbiosis in patients with RA is characterized by the loss of Bacteroidetes with an overgrowth of Prevotella copri (P. copri) in the intestine, also in patients treated with methotrexate [39,40]. This phenomenon is especially common in patients carrying the "shared epitope" [41].…”
Section: Influence Of the Microbiome On Autoimmunitymentioning
confidence: 99%